Bird Diversity Of The Crocker Range National Park, Sabah, Malaysia - MA, Rahman; MA, Salleh; Andrew Alek, Tuen (Researchgate, 2002)
A study of bird fauna was conducted at Park Headquarters of Crocker Range Park and its vicinity from 16-22 October 1999. Crocker Range Park Headquarters is located about 8 km from Keningau town. Mist-net and transect study were conducted in secondary and primaryforest. A total of 840 net/hr were deployed with total capture of 32 birds of 17 species from seven families. Of 17 species, seven species were caught in secondary forest and 13 species in primary forest. Three species were caught in both secondary and ...